The Use of Modern Intramedullary Nailing in Distal Fibula Fracture Fixation. Issue 3 (14th September 2018) - Tracey, Joseph; Vovos, Tyler; Adams, Samuel; Parekh, Selene
Category: Trauma Introduction/Purpose: Lateral malleolus (LM) fixation is necessary for unstable ankle fractures. Traditional fixation relies on the use of plates through a lateral incision, wound healing can be an issue for such incisions. A novel intramedullary (IM) fixation device has been developed that can be placed through a minimal incision. The purpose of this study was to demonstrate the clinical efficacy of this device. Methods: A retrospective analysis was performed on patients who received IM fixation for isolated fibula, bimalleolar (BM), and trimalleolar (TM) fractures. Pertinent demographic information, operative factors, complications, and clinical outcomes were recorded. Results: Sixteen patients were included in the study with an average age of 59 (Range of 35 to 86). Six patients presented with isolated LM fractures, four patients had a BM fracture with a syndesmotic injury, two patients sustained a LM fracture with an associated syndesmotic injury, two patients had a BM fracture, and two patients had a TM fracture with a syndesmotic injury. There was a 100% healing rate of the lateral malleolus without any cases of malunion or shortening. There were no cases of sural nerve or peroneal tendon injuries, nor any wound complications found. Conclusion: These findings demonstrate the safe and efficacious use of a novel intramedullary fixation device for fibula fractures with a lower wound complication and infection rates compared to published outcomes found with lateral fibular plating. The features of this device allow for reliable fixation of the fibula, maintaining length and minimizing wound issues.